Question
Asked Dec 6, 2019
26 views

What is the sum of the answers to the following unsimplified radical?

√-2x-3=√-5x-7+(−2)
check_circle

Expert Answer

Step 1

Consider the given radical equation.

help_outline

Image Transcriptionclose

2x – 3 = /-5x – 7 +(-2)

fullscreen
Step 2

Square both sides and simplify.

help_outline

Image Transcriptionclose

(V-2x – 3)' = (V-5x – 7– 2)* -2x – 3 = -5x – 4/-5x – 7 – 3 3x = -4-5x – 7 (3x)* = (-4/-5x –7 9x? = -80x – 112 9x? + 80x +112 = 0

fullscreen
Step 3

Solve the equation using ...

help_outline

Image Transcriptionclose

-80 /80² – 4(9)(112) 2(9) -80 ± /2368 18 -80 ±8/37 18 14(J37 – 10)

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Other